Relationship between personality traits and the inner strengths - Kövi Zsuzsanna; Tinakon Wongpakaran; Nahathai Wongpakaran; Pimolpun Kuntawong; Berghauer-Olasz Emőke; Бергхауер-Олас Емйовке; Mirnics Zsuzsanna (Medicinska naklada, 2021)
Abstract. Background: Zuckerman-Kuhlman-Aluja Personality questionnaire (ZKA-PQ) measures five psychobiologically based personality factors (activity, aggression, extraversion, neuroticism, and sensation seeking). The inner strength (from the ten perfections based on Theravada Buddhism) deems positive character, which includes truthfulness, perseverance, wisdom, generosity, morality (five precepts), mindfulness and meditation, patience and endurance, equanimity, determination, and loving kindness measured by the strength-based inventory (SBI). Our aim was to unfold the relationship between ZKA factors and SBI. Methods: 642 Thai (age mean = 28.27, SD = 10.61) individuals (males 26.2%, females 73.8%) filled out our questionnaire battery: (1) Zuckerman-Kuhlman-Aluja Personality questionnaire - 200 items, 20 facets, five factors: Aggressiveness, Sensation Seeking, Activity, Extraversion, Neuroticism. (Cronbach alphas: 0.88, 0.81, 0.83, 0.89, 0.91 for AG, SS, AC, EX, NEU, respectively). (2) Strength-based inventory - 10 items, measuring 10 inner strength (Cronbach alpha: 0.68). Pearson correlation, neural network modelling and person-oriented methodology (model-based clustering) were conducted for analysis. Results: Our correlational results revealed that inner strengths are negatively related to Aggression (r=-0.44**), Neuroticism (r=-0.43**), Sensation seeking (r=-0.16**), whereas positively related to Extraversion (r=0.37**) and Activity (r=0.24**). Highest correlations were found between AG and patience (-0.43**) and NEU and perseverance (r=-0.40**), both with negative sign. According to neural network modelling Activity was most related to Perseverance, Aggression to lack of Patience, Neuroticism to lack of Perseverance and Equanimity, Sensation Seeking to lack of Morality. Extraversion was most weakly related to inner strengths, but it was related to all other personality dimensions. Model based clustering revealed four typical personality profiles: resilients (41.8%), extraverted undercontrollers (29.0%), introverted undercontrollers (10.6%) and overcontrolled (18.6%). Results showed that resilients had highest inner strength levels, whereas overcontrolled ones had the lowest. Conclusion: Negative traits are, as expected, conversely related with strength, while positive traits (extraversion and activity) are positively related with strength. Our results confirm that resilient personality pattern can be linked to the inner strengths measured by SBI scale, which was based on 10 Buddhist perfections. Further results should be addressed how increase in inner strength can be related to changes in biologically based personality dimensinos towards the resilient pattern.
https://www.psychiatria-danubina.com/UserDocsImages/pdf/dnb_vol33_noSuppl%204/dnb_vol33_noSuppl%204_844.pdf
Keywords: inner strengths; Buddhism; personality; positive character; ZKA-PQ